Combined SSCP/duplex analysis by capillary electrophoresis for more efficient mutation detection - Kozlowski, Piotr (Oxford University Press, 2001)
SSCP and heteroduplex analysis (HA) continue to be the most popular methods of mutation detection due to their simplicity, high sensitivity and low cost. The advantages of these methods are most clearly visible when large genes, such as BRCA1 and BRCA2, are scanned for scattered unknown mutations and/or when a large number of DNA samples is screened for specific mutations. Here we describe a novel combined SSCP/duplex analysis adapted to the modern capillary electrophoresis (CE) system, which takes advantage of multicolor labeling of DNA fragments and laser-induced fluorescence detection. In developing this method, we first established the optimum conditions for homoduplex and heteroduplex analysis by CE. These were determined based on comprehensive analysis of representative Tamra-500 markers and BRCA1 fragments at different concentrations of sieving polymer and temperatures in the presence or absence of glycerol. The intrinsic features of DNA duplex structures are discussed in detail to explain differences in the migration rates between various types of duplexes. When combined SSCP/duplex analysis was carried out in single conditions, those found to be optimal for analysis of duplexes, all 31 BRCA1 and BRCA2 mutations, polymorphisms and variants tested were detected. It is worth noting that the panel of analyzed sequence variants was enriched in base substitutions, which are usually more difficult to detect. The sensitivity of mutation detection in the SSCP portion alone was 90%, and that in the duplex portion was 81% in the single conditions of electrophoresis. As is also shown here, the proposed combined SSCP/duplex analysis by CE has the potential of being applied to the analysis of pooled genomic DNA samples, and to multiplex analysis of amplicons from different gene fragments. These modifications may further reduce the costs of analysis, making the method attractive for large scale application in SNP scanning and screening.